The influence of perceived neighborhood disorder on HIV care-related decisions: A qualitative study - Linda Jepkoech Kimaru; Priscilla Magrath; ChengCheng Hu; Sudha Nagalingam; Elizabeth Connick; Kacey Ernst; John Ehiri (PLoS ONE, 2025)
The study used a qualitative approach to explore how perceived neighborhood disorder influences health-related decisions among people living with HIV. Recognizing the crucial role environmental factors play in health behaviors, this research seeks to bridge a gap in understanding how neighborhood dynamics affect individuals with HIV. A qualitative research design with interpretive qualitative analysis was used. The interview guide and analysis were guided by the Broken Windows Theory and Social Cognitive Theory, enabling an exploration of the intersection between environmental perceptions and healthcare behaviors. Data were collected through telephonic in-depth interviews with 18 participants from two HIV clinics from June 2022 to February 2023. Interviews were analyzed using the Dedoose software 9.0.17 and narratives were enriched using their survey data from a cross-sectional study with a validated scale to measure perceived neighborhood disorder. Our findings show that perceived neighborhood disorder influences HIV care-related decisions through a diminished sense of control pathway. Also, healthcare settings emerge as a mitigator of the influence of perceived neighborhood disorder on HIV care-related decisions by offering a sense of control. Perception of lower neighborhood disorder correlates with a strong sense of control and a preference for specialized care. As the perception of neighborhood disorder increases, there is a shift toward care settings that balance specialized services with a supportive care environment. A higher perception of neighborhood disorder leads to prioritized care settings that provide a sense of community support, and discretion, reflecting adaptations to a compromised sense of control. This research underscores the influence of neighborhood disorder on health-related decisions through the pathway of self-control, emphasizing the role that healthcare environments play as mitigators. For chronic disease management, such as with HIV, the development of healthcare settings that reinforce patient autonomy and control, alongside community efforts to diminish signs of disorder, and their underlying causes is crucial.